Influence of anatomic valve conditions and coronary flow on aortic sinus hemodynamics - Moore, Brandon L., author; Dasi, Lakshmi Prasad, advisor; Gao, Xinfeng, advisor; Kirkpatrick, Allan, committee member; Orton, Christopher, committee member (Colorado State University. Libraries, 2015)
Heart disease is the leading cause of death in the US, and aortic valve stenosis represents a significant portion of this disease. While the specific causes of stenosis are not entirely clear, its development has been strongly linked to mechanical factors such as localized solid and fluid stresses and strains, especially on the aortic side of the valve leaflets. These mechanical cues can be tied to valvular hemodynamics, however the factors regulating these hemodynamics are relatively unknown. Therefore, the overarching hypothesis of this research is that aortic valve sinus hemodynamics are regulated by anatomic valve conditions and presence of coronary flow. This hypothesis is explored through three specific aims: 1) to develop methodologies for quantifying hemodynamics within the aortic sinuses, 2) to characterize the differences in native valve flow patterns that occur due to patient and sinus variability, and 3) to evaluate the hemodynamic impacts of different prosthetic aortic valve implantations. In this work, experimental methods have been developed to study a broad range of aortic valve conditions, and computational models were also employed to validate and enhance experimental findings. An in vitro setup is presented using a surgical bioprosthesis as a native aortic valve model, while additional valve implantations were also tested. Physiological pressures and flow rates were imposed across these valves via an in-house pumping loop, which included a novel coronary flow branch. Two-dimensional time-resolved particle image velocimetry (PIV) protocols were developed and employed to analyze sinus vorticity dynamics. Computationally, both 2D and 3D simulations were run in ANSYS Fluent to enhance experimental findings. Results from this research demonstrate that aortic sinus hemodynamics are indeed regulated by anatomic valve conditions and coronary flow. From a clinical perspective, average valve geometric parameters tend to produce hemodynamics that are least likely to initiate disease than those near the upper or lower anatomical limits. Coronary flow was likewise found to increase sinus velocities and shear stresses near the leaflets, which is also beneficial for valve health. The prosthetic valves tested – transcatheter and sutureless – both severely limited sinus perfusion, which could help explain an increased risk of thrombus formation in the transcatheter case and suggests similar risk for sutureless valves. These findings could help educate clinicians on proper courses of treatment based on patient-specific valve parameters, and could also provide useful information for engineers when designing new valve prostheses.
Zip file contains supplementary videos, no sound.
Keywords: aortic valve; cardiovascular; heart; hemodynamics